2021
DOI: 10.3390/jmse9020145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Disruptive Events on Port Performance and Choice: The Case of Gothenburg

Abstract: This paper assesses the impact of a major disruptive event at the port of Gothenburg, Scandinavia’s largest container port. Automatic Identification System (AIS) data is analyzed, in combination with official port statistics on container handling in the four main container ports in Sweden, from 2014–2018. Particular attention is paid to the relationship between container volumes handled and calculated performance metrics at the specific times of the intense labour dispute at the port of Gothenburg during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…During the intense conflict, the container volumes handled in the port of Gothenburg decreased (Svanberg et al. , 2021).…”
Section: Analysis Of Supply Chain Disruptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the intense conflict, the container volumes handled in the port of Gothenburg decreased (Svanberg et al. , 2021).…”
Section: Analysis Of Supply Chain Disruptionsmentioning
confidence: 99%
“…, 2021). Other ports increased their volumes, but the total number of containers handled in Sweden decreased by 4% (Svanberg et al. , 2021).…”
Section: Analysis Of Supply Chain Disruptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…AIS data have also been employed in other data-driven applications. AIS data have been used alongside port container throughput data to assess the impact of disruptions at ports in Sweden ( 29 ). This study showed that AIS data can present the direct quantitative impacts that labor disputes may have on a port’s success.…”
Section: Literature Reviewmentioning
confidence: 99%